Memorandum of understanding between Universiti Teknologi MARA and SK Kota, Rembau, Negeri Sembilan / Fakulti Muzik - Universiti Teknologi MARA, Fakulti Muzik (Universiti Teknologi MARA (UiTM), 2020)
Memorandum of understanding on friendship, cooperation and collaboration.